1991
DOI: 10.1093/infdis/163.4.762
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Core Lipopolysaccharide Determinants: Absence of Cross-reactivity with Heterologous Lipopolysaccharides

Abstract: Using monoclonal antibodies directed against defined epitopes of endotoxin core, this study demonstrated that the presentation of lipopolysaccharide (LPS) to antibodies is critical for measuring the specific binding of antibodies to LPS structures. False cross-reactive reactions apparently were observed when free core LPS or lipid A were used as antigens in ELISA, whereas coating with complexes of high-density lipoproteins with core LPS increased both the sensitivity and the specificity of the test compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…IgGs were isolated from preimmune (control IgG) and immune (anti-LBP IgG) plasma by protein A chromatography. Since we used LPS isolated from Escherichia coli 0111 (Sigma) in our experiments, we ruled out the presence of anti-LPS 0111 antibodies in this plasma by ELISA (11) (data not shown). F(ab')2 fragments were obtained by trypsin digestion (Pierce).…”
Section: Methodsmentioning
confidence: 99%
“…IgGs were isolated from preimmune (control IgG) and immune (anti-LBP IgG) plasma by protein A chromatography. Since we used LPS isolated from Escherichia coli 0111 (Sigma) in our experiments, we ruled out the presence of anti-LPS 0111 antibodies in this plasma by ELISA (11) (data not shown). F(ab')2 fragments were obtained by trypsin digestion (Pierce).…”
Section: Methodsmentioning
confidence: 99%
“…Because the observed antibody binding to the various lipopolysaccharide preparations could be nonspecific, several additional experiments were performed. Blocking hydrophobic domains on lipopolysaccharide by complexing to other molecules has been used to suppress or eliminate nonspecific binding (1,4,23,48). Purified P. gingivalis and B. forsythus lipopolysaccharide were complexed to bovine serum albumin, polymyxin-B and apolipoprotein Al as described in the Material and methods section, and compared by ELISA to naked, uncomplexed lipopolysaccharide.…”
Section: Resultsmentioning
confidence: 99%
“…If a significant proportion of the observed binding were nonspecific, binding would have occurred from the preimmune as well as the immune rabbit serum and that was not the case. Nonspecific binding can be suppressed by complexing lipopolysaccharide to bovine serum albumin, apolipoprotein Al (one of the proteins that binds highdensity lipoproteins to lipopolysaccharide), and polymyxin-B (5,23,48). Interpretation of the results of such experiments, however, is made difficult by the fact that some of these molecules such as polymyxin-B also bind to antigenic epitopes in lipid A (3,13).…”
Section: Discussionmentioning
confidence: 99%
“…D. Baumgartner, unpublished data). By solubilization of the core glycolipid in a physiological manner to circumvent nonspecific binding [19], the 15 antisera used in one study were later shown to contain IgG and IgM antibody to 15 at a titer only threefold higher than that in control (preimmune) serum; furthermore, these antisera contained no more antibodies to lipid A than did the control serum [20]. Moreover, it now appears that antibodies to 15 are highly specific for E. coli15 and that they do not cross-react with endotoxin from other bacteria.…”
Section: Antibodies To Endotoxinmentioning
confidence: 99%